Exploring Deixis in Maroon 5's Song "Daylight": Descriptive Qualitative Research - Nasution, Sukma Septian (IJLHE: International Journal of Language, Humanities, and Education, 2023)
This study aims to analyze deixis, a pragmatic concept of linguistic reference, in Maroon 5's song "Daylight." The study utilizes descriptive qualitative methodology to analyze the deixis types in the song "Daylight," aiming to describe natural phenomena and interrelationships without theoretical constraints. The primary data source is the song's lyrics, categorized into personal, spatial, temporal, social, and discourse deixis, providing insights into the communicative and emotional impact of deixis in songwriting. The research findings reveal that the song "Daylight" by Maroon 5 effectively employs various types of deixis to establish a profound emotional connection with the audience. Personal deixis engenders intimacy, while spatial and place deixis create a vivid and relatable narrative. Temporal and time deixis evoke a sense of urgency and nostalgia, and social deixis fosters a shared emotional experience. Additionally, discourse deixis guides the audience through the unfolding events. Although the research is limited to a single song, further analysis of a diverse range of songs and audiences could provide deeper insights into deixis in music. Understanding the significance of deixis empowers songwriters to create emotionally impactful lyrics, enhancing storytelling across various artistic expressions.